Enhancement Effects of Transition and Vavilov-Cherenkov Radiation Mechanisms Under Grazing Interaction of Fast Electrons With a Thick Substrate Applied by Thin Layer - Irribarra E.; Kubankin A. S. Aleksandr Sergeevich; Sotnikov A.; Nazhmudinov R. M.; Fam T.; Starovoytov A. P. (2016, 2016)
Title screen